2016
DOI: 10.1002/mma.4149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of awareness program for controlling mosaic disease in Jatropha curcas plantations

Abstract: The shrinkage of fossil fuel resources motivates many countries to search alternative energy sources. Jatropha curcas is a small drought‐resistant shrub from whose seeds a high grade fuel biodiesel can be produced. It is cultivated in many tropical countries including India. However, the plant is affected by the mosaic virus (Begomovirus) through infected white‐flies (Bemisia tabaci) which causes mosaic disease. Disease control is an important factor to obtain healthy crop but in agricultural practice, farming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Penelitian yang sudah pernah dilakukan sebelumnya, antara lain oleh Venturino dkk (2016) [6] yang mengkontruksi model penyebaran penyakit mosaic pada jarak pagar dan memodifikasi dengan memberikan kontrol pemberian pestisida. Selain itu penelitian yang dilakukan oleh Basir dkk (2016) [7] yang mengkontruksi model matematika penyebaran penyakit mosaic pada jarak pagar. Model ini dimodifikasi dengan memberikan kompartemen populasi manusia aware.…”
Section: Pendahuluanunclassified
“…Penelitian yang sudah pernah dilakukan sebelumnya, antara lain oleh Venturino dkk (2016) [6] yang mengkontruksi model penyebaran penyakit mosaic pada jarak pagar dan memodifikasi dengan memberikan kontrol pemberian pestisida. Selain itu penelitian yang dilakukan oleh Basir dkk (2016) [7] yang mengkontruksi model matematika penyebaran penyakit mosaic pada jarak pagar. Model ini dimodifikasi dengan memberikan kompartemen populasi manusia aware.…”
Section: Pendahuluanunclassified
“…For instance, authors in [13] consider how allowing surroundings for connections among farmers, researchers, and other factors, can donate to reduce existing problems related with the crop. Al Basir et al, describe the participation of farming communities in Jatropha projects for biodiesel construction and guard of plants from mosaic disease, using a mathematical model to predict the growth of renewable power resources [14].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, as one of the most suitable alternative renewable energy resources, it is widely planted in many countries [2,3]. However, many studies showed that Jatropha plants are hosts of mosaic virus which is a main cause of the occurrence of viruses in Jatropha curcas [4,5].…”
Section: Introductionmentioning
confidence: 99%